SIMULTANEOUS DETERMINATION OF Zn, Cd, Pb AND Cu IN MUSHROOMS BY DIFFERENTIAL PULSE ANODIC STRIPPING VOLTAMMETRY - COVACI, Enikő; DARVASI, Eugen; PONTA, Michaela (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The present work presents the optimization of differential pulse anodic stripping voltammetry with hanging mercury drop electrode for the determination of Zn, Cu, Cd and Pb in mushrooms. The optimized method was characterized in terms of limits of detection and quantification, accuracy and precision and applied for the analysis of 4 food supplements (Chaga and Shiitake powders; Reishi tablets and capsules containing a Mixture of mushroom extracts) and a fresh mushroom (King bolete (Boletus Edulis)). The concentrations of Zn and Cu as essential elements were discussed in relation with the recommended daily allowance, while Cd and Pb compared with maximum acceptable levels of toxic elements set in the European legislation. It has been found that fresh mushroom King bolete (100 g serving per day) represents a more significant source of Cu and Zn than food supplements, namely up to 24% and 10% from the recommended daily allowance. The concentration of Cd (0.09-0.69 µg g-1) and Pb (1.83-3.60 µg g-1) in the edible King bolete fungus and food supplements revealed no human health risk, since they were below 1.5 mg provisional tolerable monthly intake (Cd) and 72 mg/day (Pb) for 60 kg body weight.